Active diazonium-modified zeolite fillers for methacrylate-based composites. Issue 7 (3rd July 2019) - Sandomierski, Mariusz; Okulus, Zuzanna; Voelkel, Adam
ABSTRACT: The surface properties of the fillers have a significant effect on the mechanical properties of the composites. Despite many uses of diazonium interface chemistry, it has rarely been used in the modification of fillers, although it has much to offer. In this work zeolite surface was modified by 4-(dimethylamino)benzenediazonium cation to obtain an active filler having dimethylamino groups for potential further applications. Modification effectiveness was determined by means of scanning-electron microscopy, energy-dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy. All applied methods confirmed the presence of an organic layer on the surface of modified zeolite, thereby the success of modification. A modified material was applied as an active filler in a methacrylic-resin-based photocurable composites which are mainly used in many dental applications. To verify the active properties of a zeolite filler some mechanical properties, as well as crosslinking ability were examined. All conducted tests proved that the addition of some amount of modified filler is beneficial for the final composite.